2015
DOI: 10.5152/tftrd.2015.76093
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Quality of Life, Functional Capacity, and Depression Level after Cardiac Rehabilitation

Abstract: Objective: In cardiac rehabilitation program (CRP), patients are supported to achieve and maintain optimal physical and psychosocial health following a recent cardiac event or procedure. In this study, we aimed to retrospectively assess the effects of CRP in our cardiopulmonary rehabilitation unit. Material and Methods: Records of 40 patients with a diagnosis of coronary artery disease (CAD) and 10 patients who had undergone coronary artery bypass graft surgery (CABG) and who completed 30 sessions were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
1
2
0
5
Order By: Relevance
“…In a study on the assessment of 30 sessions of CR on quality of life, functional capacity in CAD patients who underwent CABG, a significant improvement was observed in exercise capacity, functional capacity, quality of life scales. Only CAD patients had significant improvement in depression level after CR [35]. Similar to that study, we observed a significant improvement in SF-36 quality of life scale and functional activity in our patients.…”
Section: Discussionsupporting
confidence: 90%
“…In a study on the assessment of 30 sessions of CR on quality of life, functional capacity in CAD patients who underwent CABG, a significant improvement was observed in exercise capacity, functional capacity, quality of life scales. Only CAD patients had significant improvement in depression level after CR [35]. Similar to that study, we observed a significant improvement in SF-36 quality of life scale and functional activity in our patients.…”
Section: Discussionsupporting
confidence: 90%
“…Развитие современной медицины ставит задачу приближения качества жизни реципиентов внутренних органов к таковой в популяции здоровых лиц. Изучению этого вопроса посвящены многочисленные зарубежные исследования [5,[7][8][9][10][11][12]. При анализе литературы последних 15 лет о качестве жизни реципиентов печени в базе Medline и крупнейшей отечественной электронной библиотеки научных публикаций (е-library) нами найдены единичные исследования в трансплантационных центрах России [13,14] и большое количество зарубежных работ, посвященных этому вопросу [10,11,[15][16][17].…”
Section: Discussionunclassified
“…В данных обстоятельствах, наряду с объективными показателями здоровья, определенный интерес приобретает субъективная оценка качества жизни реципиентов. В зарубежных исследованиях КЖ реципиентов печени авторами подчеркивается значимость улучшения КЖ как важного итогового результата (major outcome) для оценки успеха трансплантации в отдаленном послеоперационном периоде [4,5].…”
unclassified
“…Несмотря на очевидное снижение КЖ у пациентов с ХСН, объективное измерение динамики этих по-казателей является непростой задачей. Ряд авторов предлагают использовать для оценки состояния КЖ после ТС: Geissen Subjective Complaints List (GBB), Medication Experience Scale for Immunosuppressants (MESI), General Health Questionnaire (GHQ, италь-янская версия), шкалу оценки тревоги и депрессии Бека [9,[28][29][30]. Однако в литературе недостаточно публикаций об эффективности применения данных опросников.…”
Section: Discussionunclassified
“…Кроме того, не все из них разрешены для использования в РФ. Многие авторы предлага-ют оценивать КЖ у реципиентов после ТС опрос-ником SF-36 [6,9,13,28,29,31], который в отличие от вышеперечисленных опросников неспецифичен и понятен всем пациентам. В этой связи у наших пациентов для оценки КЖ использован данный оп-росник.…”
Section: Discussionunclassified